Optimalisasi Usaha Untuk Keberhasilan UMKM Di Desa Kertonegoro - Achadyah Prabawati; Nava Rindi Anisa Putri (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Business is an activity that cannot be avoided by all people in life in the world. Socialization is a form of community activity in communicating. So that humans in society are always faced with socializing conditions by always communicating with their relatives.MSMEs have a vulnerable business arena, so in life they are faced with the threat of setbacks. That is the attack of competitors so that they experience setbacks. What must be maintained, which is maintained is the level of operational activities, and the level of antidote to setbacks, as well as the level of vigilance in the business program. The business program cannot be separated from recording and procuring debt. This can be done vigilantly so that they are motivated to earn so that they are able to pay off debts. Why should note. Actually recording is to be able to compare something in the past with the present. This condition can be used as a benchmark for increasing success.DesBy recording, it can be analyzed how the business achievements that have been carried out. This business achievement can be used as a benchmark for the success of a business.